The post-legal ethics of Tariq Ramadan: persuasion and performance in Radical reform: Islamic ethics and liberation - March, Andrew F. (Middle East Law and Governance, 2010)
Rezension von: Ramadan, Tariq: Radical reform: Islamic ethics and liberation. - Oxford : Oxford Univ. Pr., 2009